Sleep Disturbances in Pediatric Craniopharyngioma: A Systematic Review - Cordani, Ramona; Veneruso, Marco; Napoli, Flavia; Di Iorgi, Natascia; Milanaccio, Claudia; Consales, Alessandro; Disma, Nicola; De Grandis, Elisa; Maghnie, Mohamad; Nobili, Lino (Frontiers in Neurology, 2022)
Craniopharyngiomas are rare brain tumors of the sellar region and are the most common non-neuroepithelial intracerebral neoplasm in children. Despite a low-grade histologic classification, craniopharyngiomas can have a severe clinical course due to hypothalamic involvement. The hypothalamus plays a crucial role in regulating vital functions, and it is a critical component of the sleep-wake regulatory system. This systematic review aims to provide an overview of the current knowledge on sleep disorders in patients with craniopharyngioma to unravel their underlying mechanisms and identify possible therapeutic strategies. A comprehensive electronic literature search of the PubMed/MEDLINE and Scopus databases was conducted in accordance with the PRISMA® statement. Extensively published, peer-reviewed articles involving patients with childhood craniopharyngioma and focused on this specific topic were considered eligible for inclusion. Thirty-two articles were included; a high prevalence of excessive daytime sleepiness was reported in CP patients, with wide variability (25-100%) depending on the diagnostic method of detection (25-43% by subjective measures, 50-100% by objective investigations). In particular, secondary narcolepsy was reported in 14-35%, sleep-disordered breathing in 4-46%. Moreover, sleep-wake rhythm dysregulation has been notified, although no prevalence data are available. Possible mechanisms underlying these disorders are discussed, including hypothalamic injury, damage to the suprachiasmatic nucleus, low melatonin levels, hypocretin deficiency, and hypothalamic obesity. The diagnosis and management of sleep disorders and associated comorbidities are challenging. This review summarizes the pathophysiology of sleep disorders in childhood-onset CP and the main treatment options. Finally, a possible diagnostic algorithm in order to accurately identify and treat sleep disorders in these patients is proposed.